Awareness among glaucoma patient at upper Egypt - A. M. Mansour, Magda; Abd El-aziz, Nermeen Mahmoud; Mekkawy, Mimi; M. Ahmed, Rania (International Journal of Advanced Nursing Studies, 2016)
Aim: To assess the awareness among glaucoma patients at Upper Egypt Governorate hospitals.Research design: Descriptive cross sectional research design was used in this studySetting: The study was conducted in ophthalmology outpatient clinics (male & female) at Assiut University Hospital & Al-rmad Hospital, Elmina and Sohag Governorate.Subjects: The sample of this study total coverage of glaucoma patients included (1000), the researcher taking the sample during one year, this sample aged 50 years and above.Tool of study: One tool was used in this study include three parts, part I: patient demographic characteristics, part II: medical data, part III: knowledge about risk factors and self-practice regard glaucoma.Results: The most of patients age ranged between 60:80 year, nearly three quarter (74.6%) of them were females, and 80% of them comes from urban areas. The majority of studied sample (84.5%) unaware about glaucoma disease and show statistical significant difference between awareness of them and their education, Pâ‰¤0.05. Also, there was no significant difference between knowledge of studied sample and their residence.Conclusion: The majority of glaucoma patients complain from poor of knowledge & practice.Recommendation: Design & implement of health educational program about glaucoma are needed to improve patient knowledge & practice regard glaucoma.